Boosting Production Performance Through Employee Empowerment and Sense of Belonging: A Case Study at PT Batu Gunung Mulia Putra Agro - Zulkarnain, Iskandar; Claudia, Meiske (Universitas Proklamasi 45, 2025)
This study examines how employee empowerment influences production employees’ performance, with sense of belonging serving as a mediating mechanism. In competitive operations, empowerment that grants autonomy, recognizes contributions, and invites participation in decisions is expected to strengthen attachment to the organization and, in turn, productivity. The study contributes evidence from Indonesia’s agro-manufacturing sector, an important yet underexamined context. A quantitative explanatory design was employed. Relationships among constructs were estimated using Partial Least Squares Structural Equation Modeling. The population consisted of 98 production employees at PT Batu Gunung Mulia Putra Agro; total sampling yielded 42 respondents, including 40 employees and two supervisors. Data were collected through a structured questionnaire on a five-point Likert scale. Results indicate that empowerment significantly increases both sense of belonging and performance. Sense of belonging also exerts a positive effect on performance and mediates the relationship between empowerment and performance, suggesting an indirect pathway from empowerment to outcomes. Model diagnostics show accuracy, with R-square values of 0.631 for sense of belonging and 0.856 for performance. These findings imply that autonomy, recognition, and participatory decision-making are effective levers for cultivating emotional bonds and sustaining productivity. Organizations are encouraged to institutionalize empowerment-based policies to enhance performance.